Effect of Monotherapy and Combination Therapy of Pantoprazole and Aprepitant in Gastric Esophageal Reflux Disease in Albino Rats - Kamleshwar Shukla; Prince Raj; Arun Kumar; Mukesh Kumar; Gaurav Kaithwas (The Scientific World Journal)
The present study was undertaken to elucidate the effect of pantoprazole and aprepitant on experimental esophagitis in albino rats. Groups of rats, fasted overnight, received normal saline (3 mL/kg, sham control) or toxic control (3 mL/kg) or pantoprazole (30 mg/kg) or aprepitant (10 mg/kg), or their combinations and were subjected to pylorus and forestomach ligation. Animals were sacrificed after 8 h and evaluated for the gastric pH, volume of gastric juices, total acidity, esophagitis index, and free acidity. Esophageal tissues were further subjected to estimations of TBARS, GSH, catalase, and SOD. Treatment with pantoprazole and aprepitant significantly inhibited the gastric secretion, total acidity, and esophagitis index. The treatment also helped to restore the altered levels oxidative stress parameters to normal.